Black Holes : proceedings of the Space Telescope Science Institute Symposium, held in Baltimore, Maryland, April 23-26, 2007 - Livio, Mario, 1945-; Koekemoer, Anton (Space Telescope Science Institute Symposium Series, 21., 2011)
A collection of review papers exploring the astrophysics of black holes, providing an invaluable resource for researchers and graduate students.